Quebra dinâmica da simetria quiral como possível mecanismo gerador da massa do bóson de Higgs - Yuri Rodrigues Batista (2012)
The Standard Model aims at unifying electromagnetic and weak interactions. It is a renormalizable eld theory that uses spontaneous symmetry breaking to generate mass for the weak mediators, via the Higgs mechanism. In this context, the model raises up the following question: is the Higgs boson an elementary or composite particle? In the present work, we study the second alternative, by investigating a proposal by W. A. Bardeen et. al[2], which considers a Nambu-Jona-Lasinio type model in which a quartic interaction among quarks su ers a dynamical chiral symmetry breaking, and generates a tt condensate. T. Gherghetta et al.[6] veri ed that the calculations done by W. A. Bardeen et al. [2] presented ambiguities for integrals with divergence greater than logaritmic. In the present work we show that these ambiguities turn out to be surface integrals with null value if one chooses an appropriate regularization scheme. Our approach consists of using implicit regularization, with the constraints that energy and momentum are conserved for all vertices and for all routing in the Feynman diagrams.